Improvement of physical preparedness of qualified volleyball players - Hnatchuk, Y.; Lynets, M.; Khimenes, K.; Pityn, M. (Journal of Physical Education and Sport, 2018)
Systematic training by a rationally-developed program of physical training of qualified volleyball players with consideration to individual profiles and model parameters of physical preparedness can guarantee efficient development of adaptation processes and physical qualities. The aim of the paper is to define efficiency of improvement of physical preparedness of qualified volleyball players via application of multidirectional approaches to differentiation of their physical training. Results. Comparison of training influences of different methodologically-oriented programs of differentiated physical training of qualified volleyball players by 20 indices of physical preparedness throughout doubled macrocycle proves their different efficiency. The program of differentiated physical development of insufficiently developed physical qualities regarding individual profile of physical preparedness of each athlete caused more positive changes of physical preparedness of qualified volleyball players in 11,4% of cases. Throughout the first competition period of the doubled macrocycle, true positive changes ("`.0,05.0,001) occurred in three put of eleven indices of general physical preparedness with volleyball players EG-1, while with volleyball players EG-2 . in four out of eleven indices. At the level of special physical preparedness development with volleyball players EG-1, true ("`.0,05.0,001) results increased in eight out of nine indices, while with volleyball players EG-2, the results increased in seven out of nine indices. Throughout the second training period of the doubled macrocycle, true positive changes ("`.0,05.0,001) occurred in six out of eleven indices of general physical preparedness with volleyball players EG-1, while with volleyball players EG-2, true positive changes ("`.0,001) occurred only in one index. At the level of development of special physical preparedness, true results ("`.0,05.0,001) increased with athletes EG-1 in four out nine indices, while with athletes EG-2 . in three out of nine indices.